Shiga toxin producing Escherichia coli (STEC) in cattle: factors affecting fecal shedding of E. coli O157:H7 and detection methods of non-O157 STEC - Paddock, Zachary Dean (Kansas State University, 2013)
Escherichia coli O157:H7 and over 380 non-O157 serotypes of Shiga toxin producing E. coli (STEC) are human food-borne pathogens that inhabit the hindgut of ruminants and are shed in the feces, which subsequently contaminate food products. Recent epidemiological data have shown that six non-O157 STEC (O26, O103, O111, O121, O45 and O145) account for majority of human STEC infections. Fecal shedding of STEC is influenced by a number of factors, including diets, supplements, and feed additives, because of their potential to alter hindgut ecosystem. Not much is known about the fecal shedding of non-O157 STEC in cattle because of lack of standardized detection methods. Fecal shedding of E. coli O157:H7 was studied to determine the effects of supplemental urea, monensin, an ionophore, and ractopamine, a beta-agonist. Cattle fed monensin at 44 mg/kg of feed had lower (P = 0.05) fecal O157:H7 prevalence than cattle fed 33 mg/kg. Supplemental urea (0.35 or 0.70% of the diet) and inclusion of ractopamine at 200 mg/animal/day had no effect on fecal shedding of E. coli O157:H7. In an experimental inoculation study, inclusion of corn starch to a distiller’s grains (DG)-supplemented diet had no effect on fecal shedding of E. coli O157 suggesting that either the decreased starch content in the DG-supplemented diet is not a factor in the increased shedding of E. coli O157:H7 or inclusion of pure starch in the diet may not have achieved our intended goal to have starch flow into the hindgut similar to that of corn grain. A multiplex PCR to detect O26, O45, O103, O111, O121, O145, and O157 was designed and applicability to detect the seven serogroups in cattle feces was evaluated. A multiplex PCR, designed to detect E. coli O104, feces showed presence of O104 in cattle feces (20.6%), but the isolated strains did not carry genes characteristic of the virulent strain responsible for the 2011 food-borne outbreak in Germany. Two preharvest interventions, a siderophore receptor and porin proteins-based vaccine and a Lactobacillus acidophilus-based direct-fed microbial, intended to control E. coli O157, had no effect on fecal shedding of O26 assessed by culture-based or PCR-based method.
Keywords: Pre-Harvest Food Safety; E. coli; Cattle; Animal Sciences (0475); Veterinary Medicine (0778)